Mutual AID, Environmental Policy, and the Regulation of Faroese Pilot Whaling. Issue 3 (November 2015) - Fielding, Russell; Davis, John E.; Singleton, Benedict E.
This paper examines the evolution of unwritten regulations and formal government policies in the control of the Faroese pilot whale drive, or grindadráp . This form of whaling has occurred in the Faroe Islands since at least the sixteenth century, probably much longer. Informed by theories of anarchist geography, we discuss specific policies, both formal and informal, regulating when and where whales may be pursued, actions of whalers in boats and onshore, equipment permitted for use, and the distribution of meat and blubber from the hunt that have developed over the centuries in response to internal or external pressures and calls for change. Our discussion gives special attention to a recent change in the regulation of grin-dadráp, namely the requirement, beginning in 2015, that whalers who participate in the killing process—as distinct from other aspects of whaling—be certified as having attended a training course on the subject. We conclude with a discussion of lessons learned through a reading of anarchist geographies as applied to the topic at hand.